Ethical Questions on AI-Generated Literature: The Evolution of Literary Creativity in the Post-Humanistic Era - Setiawan, Rahmat; Nuryanto, Agung Benta Febria; Pechinthorn, Komm (Humanis, 2025)
This study aims to examine the involvement of AI, particularly ChatGPT, in the creation of literary works, as well as its implications for the concepts of authorship, originality, the creative process, and the future of literature with technology. This study uses Barthesian Authorship concept and Floridi’s Ethics of Technology. The method used is a mixed method with a parallel convergent design approach. Data collection techniques include a survey of 50 students who have written literary works as part of their coursework and semi-structured interviews with three literature professors from different epistemological backgrounds. Quantitative analysis uses descriptive statistics, while qualitative data is analysed thematically. The results of the study show that all student respondents have used AI to write literary works, and the majority claim these works as their own without mentioning AI’s involvement in the process, reflecting an ethical crisis and creative subjectivity. The results of the interviews revealed that the concept of authorship has shifted from a single authority to a collaborative and negotiated relationship between humans and machines; originality is no longer considered an absolute value but rather a constantly evolving construction; the creative process must maintain its existential value; and literary ethics must be re-evaluated in the context of the current digital and academic landscape. This is literature in the post-humanist era, where AI is not merely a technological tool but a cultural agent involved in reshaping the contemporary literary landscape.